2018
DOI: 10.11301/jsfe.18522
|View full text |Cite
|
Sign up to set email alerts
|

Seasoning Production from the Residual Waste Solution of Isada Krill Processing by Its Treatment under Subcritical Water Conditions

Abstract: The residual waste solution obtained during the recover y of functional components from Isada krill was treated under subcritical water conditions. Properties of the treated solution, such as solid, protein, and carbohydrate contents, were measured. The characteristic smell of the solution was evaluated. The smell intensity increased with a rise in the treatment temperature by gasification of the soluble components. In particular, the treatment at 160-180℃ strengthened the shrimp-like fragrant smell and retain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…We have previously demonstrated that treatment of residual waste solution from Isada processing with subcritical water at 160-180℃ reduced fishy odor and enhanced its shrimp-like flavor [8]. This method is believed to be applicable to the production of shrimp-like seasonings from the aqueous residue [8].…”
Section: Krill (Euphausia Pacifica) Inhabits the North Pacificmentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously demonstrated that treatment of residual waste solution from Isada processing with subcritical water at 160-180℃ reduced fishy odor and enhanced its shrimp-like flavor [8]. This method is believed to be applicable to the production of shrimp-like seasonings from the aqueous residue [8].…”
Section: Krill (Euphausia Pacifica) Inhabits the North Pacificmentioning
confidence: 97%
“…Because the subcritical water has a lower dielectric constant and higher ionic product than ambient water, its use as a reaction solvent and extractant has attracted attention [6,7]. We have previously demonstrated that treatment of residual waste solution from Isada processing with subcritical water at 160-180℃ reduced fishy odor and enhanced its shrimp-like flavor [8]. This method is believed to be applicable to the production of shrimp-like seasonings from the aqueous residue [8].…”
Section: Krill (Euphausia Pacifica) Inhabits the North Pacificmentioning
confidence: 99%
“…Gas chromatography mass spectrometr y analysis of the odor was performed in the same manner as in our previous studies [11,12] The powdered seasoning is likely to be often used by dissolving it in water such as soup. However, since the smell of the powdered seasoning seems to affect consumers' behavior to use, sensory evaluation was performed on the powder.…”
Section: Gas Chromatographymass Spectrometry (Gc-ms) Analysis Of the mentioning
confidence: 99%
“…We have previously reported that the treatment of Isada krill [6][7][8][9][10], or that of its residual waste solution [11], under subcritical water conditions at 140-200℃ reduced the fishy odor and enhanced shrimp-like flavor.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these characteristics, subcritical water has attracted a signifi-cant amount of attention as a reaction solvent and extractant. We have previously reported that the treatment of Isada krill [8][9][10][11][12] or its residual waste solution [13] under subcritical water conditions at 140 to 200℃ reduced the fishy odor and enhanced shrimp-like flavor.…”
Section: Introductionmentioning
confidence: 99%